2022
DOI: 10.1002/agj2.21193
|View full text |Cite
|
Sign up to set email alerts
|

Residue management and genotype effect on sunn hemp organic matter and nitrogen decomposition

Abstract: Sunn hemp (Crotalaria juncea L.) is a warm‐season legume often used as a cover crop; however, there is limited information about nutrient cycling of sunn hemp residue. The objective of this study was to evaluate the effect of sunn hemp genotype and residue management on plant characteristics, decomposition, and suppression of Fusarium, Pythium, Sclerotinia, and Sclerotium microbe species. Two field experiments were conducted in Ona, FL. In Experiment 1, treatments were the split‐plot arrangement of three sunn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
(89 reference statements)
0
0
0
Order By: Relevance
“…This may be due to the higher microbial activities in buried conditions, as discussed above, where a higher N demand is required by soil microorganisms to support their own growth. Previous studies reported that plant residue C/N values higher than 45 [26] and 40 [27] are required for net N immobilization. Therefore, additional N may be required to meet crop demand approximately 1 month after bagasse is incorporated into the soil.…”
Section: Nutrient Release Patternsmentioning
confidence: 97%
“…This may be due to the higher microbial activities in buried conditions, as discussed above, where a higher N demand is required by soil microorganisms to support their own growth. Previous studies reported that plant residue C/N values higher than 45 [26] and 40 [27] are required for net N immobilization. Therefore, additional N may be required to meet crop demand approximately 1 month after bagasse is incorporated into the soil.…”
Section: Nutrient Release Patternsmentioning
confidence: 97%